2010
DOI: 10.1093/jxb/erq148
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a pathogenesis-related protein 4 (PR-4) induced in Capsicum chinense L3 plants with dual RNase and DNase activities

Abstract: Resistance conferred by the L3 gene is active against most of the tobamoviruses, including the Spanish strain (PMMoV-S), a P1,2 pathotype, but not against certain strains of pepper mild mottle virus (PMMoV), termed as P1,2,3 pathotype, such as the Italian strain (PMMoV-I). PMMoV-S induces a hypersensitive reaction (HR) in C. chinense PI159236 plant leaves with the formation of necrotic local lesions and restriction of the virus at the primary infection sites. In this paper, a C. chinense PR-4 protein induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 78 publications
(116 reference statements)
6
46
0
2
Order By: Relevance
“…It was reported that RNase activity was higher in diseased (Green 1994, Lusso and Kuc 1995, Galiana et al 1997, Hugot et al 2002, Šindelářová et al 2002, Šindelář and Šindelářová 2005 and mechanically wounded plants (Ye and Droste 1996, Lers et al 1998, LeBrasseur et al 2002. Recently it was shown that the Capsicum chinense PR-4 protein does not have chitinase activity, as previously proposed for PR-4 proteins, instead, it has both RNase and DNase activity (Guevara-Morato et al 2010). …”
Section: ⎯⎯⎯⎯mentioning
confidence: 62%
“…It was reported that RNase activity was higher in diseased (Green 1994, Lusso and Kuc 1995, Galiana et al 1997, Hugot et al 2002, Šindelářová et al 2002, Šindelář and Šindelářová 2005 and mechanically wounded plants (Ye and Droste 1996, Lers et al 1998, LeBrasseur et al 2002. Recently it was shown that the Capsicum chinense PR-4 protein does not have chitinase activity, as previously proposed for PR-4 proteins, instead, it has both RNase and DNase activity (Guevara-Morato et al 2010). …”
Section: ⎯⎯⎯⎯mentioning
confidence: 62%
“…The PR4 protein genes identified for the first time were named win-1 and win-2, which are tandemly located on the potato genome and encode two wound-inducible proteins with high homology to each other (Stanford et al, 1989). Since then, a number of PR4 protein genes have been identified from different plant species such as tomato, tobacco, Arabidopsis, Chinese cabbage, wheat, Capsicum chinense, and maize (Linthorst et al, 1991;Caruso et al, 1993;Potter et al, 1993;Bravo et al, 2003;Park et al, 2005;Guevara-Morato et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The supernatant of protein samples containing about 25 lg proteins was loaded onto gel wells. Arrowheads are pointing to absent or present of polypeptides due to virus infection reported in other works(Radwan et al 2007;Elvira et al 2008;Guevara-Morato et al 2010). Plants responded to pathogen attack by formation of new families of proteins called PRs.…”
mentioning
confidence: 84%